When calls the heart. The heart of homecoming. [videorecording (DVD)] - Loughlin, Lori; Lissing, Daniel, 1981-; Krakow, Erin; Wagner, Jack, 1959-; Oke, Janette, 1935- (When calls the heart, season 5, movie 1, 2018)
The citizens of Hope Valley find the true meaning of the season with a Wishing Tree that, through the magic of the holiday, helps everyone's wishes come true. And for Elizabeth, this means having Jack back. Together they help Robert with a family problem, while Abigail, Bill and the other people from Hope Valley work together to create a special Christmas parade that warms the hearts and brings everyone together.